The association between major dietary patterns at dinner and obesity in adults living in Tehran: A population-based study - Akbarzade, Zahra (J Cardiovasc Thorac Res, 2020)
Introduction: Findings of studies on the association between evening meal and obesity are inconclusive. Thus, we sought to investigate the association between major dietary patterns at evening meal and obesity among apparently healthy adults in Tehran. Methods: This cross-sectional research was conducted using 833 adult men and women who lived in Tehran (age range: 20-59 years). Their dietary intake was evaluated by three, 24-h dietary recalls(24hDRs), and major patterns were identified using exploratory factor analysis. The association between major dietary patterns at dinner with general and central obesity was assessed using logistic regression analysis. Results: We identified 3 major dietary patterns at dinner including "prudent", "potatoes and eggs" and"Western" patterns. There was no significant relationship between prudent and general obesity (OR:0.76, 95% CI = 0.21, 1.15, P value = 0.20), and, a significant association was not observed between potatoes and eggs and general obesity (OR: 0.89, 95% CI = 0.60, 1.32, P value = 0.57) also, there was no significant relationship between Western dietary pattern and general obesity in this study (OR: 0.95,95% CI = 0.63, 1.43, P value = 0.82). Further analyses showed that there was no significant relationship between central obesity with any of the dietary patterns. Conclusion: The results of this study do not support a possible relationship between major dietary patterns at dinner with general and central obesity. However, the presented findings should be confirmed in prospective studies.